Climate-driven longitudinal trends in pasture-borne helminth infections of dairy cattle. Issue 13 (December 2016) - Charlier, Johannes; Ghebretinsae, Aklilu H.; Levecke, Bruno; Ducheyne, Els; Claerebout, Edwin; Vercruysse, Jozef
Graphical abstract: Highlights: An 8 year cohort study investigated climate-driven trends of helminth infections in cattle. Levels of exposure to Fasciola hepatica decreased over time. Levels of exposure to Ostertagia ostertagi increased over time. Observed patterns can be explained by weather factors. Empirical research complements long-term predictions from normative models. Abstract: Helminth parasites of grazing ruminants are highly prevalent globally and impact negatively on animal productivity and food security. There is a growing concern that climate change increases helminth disease frequency and intensity. In Europe, these concerns stem from case reports and theoretical life cycle models assessing the effects of climate change scenarios on helminth epidemiology. We believe this study is the first to investigate climate-driven trends in helminth infections of cattle on a cohort of randomly selected farms. One thousand, six hundred and eighty dairy farms were monitored over an 8 year period for the two major helminth infections in temperate climate regions and climate-driven trends were investigated by multivariable linear mixed models. The general levels of exposure to Fasciola hepatica decreased over the study period while those to Ostertagia ostertagi increased, and this could at least be partially explained by meteorological factors (i.e. the number of rainy (precipitation >1 mm) and warm days (average daily temperature >10 °C) in a year). The longitudinal trends varied according to the altitude and the agricultural region of the farm. This study shows that longitudinal epidemiological data from sentinel farms combined with meteorological datasets can significantly contribute to understanding the effects of climate on infectious disease dynamics. When local environmental conditions are taken into account, the effects of climate change on disease dynamics can also be understood at more local scales. We recommend setting up a longitudinal sampling strategy across Europe in order to monitor climate-driven changes in helminth disease risk to inform adaptation strategies to promote animal health and productivity.